Seeking for ‘Self-Help’: Cross Cultural Dialogue with Sarvodaya Sri Lanka and Salvation Centre Cambodia - Yokoyama, Taizo; Ariyaratne, Vinya; Chea, Ven Som (International Journal Of Community Medicine And Public Health, 2017)
Background: The term ‘Self-Help’ has been attracting the attention of scholars across the globe,invested in sustainable-development especially after the Sustainable Development Goals (SDGs) were established by the United Nations in 2016. In this study, a joint discussion between NGOs from two nations, Sri Lanka and Cambodia was conducted to look into the successful factors in Self-Help development and the current challenges in both nations. Methods: In addition to literature reviews for theoretical discussion, the research sets the international dialogue in 23th May 2017 between Sarvodaya Sri Lanka and Salvation Centre Cambodia (n=7). The author also visited the local offices of Sarvodaya in Trincomalie and Batincaloa districts in Sri Lanka and interviewed the local officers (n=10) in addition to JICA (Japan International Cooperation Agency) volunteers (n=2) who work in a field of community welfare. In each district, five villagers (n=10) selected via snow ball sampling were also interviewed. Results: Self-Help starts from spiritual awareness, which leads to collective thinking and community practice. It is a crucial process to bring about change in a community through self-determination. Sarvodaya Sri Lanka has maintained its philosophy for decades and this implication provides an important perspective for the current challenges in Cambodia. The lessons learned from Sarvodaya punctuate ‘collective thinking’ and ‘integrated idea’ in implementing a holistic approach, recognized as strong impacts for Self-Help development. Conclusions: Being the key factor for sustainable development through Self-Help effort, collective thinking to define the issues is perceived to play a critical role in promoting integrated/holistic development.